The effect of metal ions on photocatalytic performance based on an isostructural framework1. Issue 28 (28th July 2015) - Shao, Zhichao; Huang, Chao; Han, Xiao; Wang, Huarui; Li, Angran; Han, Yanbing; Li, Kai; Hou, Hongwei; Fan, Yaoting
<x xml:space="preserve">Abstract</x> The different central metal ions in CPs have a variety of electronic configurations, which can produce a great impact on the photocatalytic properties.